Princess Academy [compact disc, unabridged] - Hale, Shannon (Hale, Shannon. Princess Academy (Series), 2007)
While attending a strict academy for potential princesses with the other girls from her mountain village, fourteen-year-old Miri discovers unexpected talents and connections to her homeland.